Carcinogenesis from chronic exposure to radio-frequency radiation - Lin, James C. (Frontiers in Public Health, 2022)
The past two decades have seen exponential growth in demand for wireless access that has been projected to continue for years to come. Meeting the demand would necessarily bring about greater human exposure to microwave and radiofrequency (RF) radiation. Our knowledge regarding its health effects has increased. Nevertheless, they have become a focal point of current interest and concern. The cellular mobile telephone and associated wireless communication technologies have proven beyond any debate their direct benefit to people. However, as for the verdict on the health and safety of billions of people who are exposed to unnecessary levels of RF radiation over extended length of time or even over their lifetime, the jury is still out. Furthermore, there are consistent indications from epidemiological studies and animal investigations that RF exposure is probably carcinogenic to humans. The principle of ALARA — as low as reasonably achievable — should be followed as a strategy for RF health and safety protection.